Correlation of Regional Differences in the Prevalence and Types of Chronic Diseases among Middle-aged and Elderly People with Health Resources Allocation in China - LIU Ying, JIANG Juncheng, JING Huiquan (Zhongguo quanke yixue, 2024)
Background China is gradually entering an ageing society and the health of the middle-aged and elderly is a growing concern, with chronic diseases such as hypertension, diabetes, coronary heart disease and stroke becoming major health threats. At the same time, the uneven distribution of health resources has led to regional differences in medical level and service quality. Objective To explore the correlation between the prevalence of chronic diseases, regional differences in the types of diseases and health care resources among middle-aged and elderly people in China. Methods A total of 19 520 middle-aged and older adults ≥45 years of age were selected by cleaning, organizing and statistically analyzing the data from the China Health and Retirement Longitudinal Study (CHARLS) 2018 from October 2022 to March 2023, and 2018 statistics from the China Health Statistics Yearbook (2011-2020) were selected as the corresponding data related to health resources. Multiple linear regression analysis was used to analyze the correlation between Theil index of the number of beds, number of health technicians [practicing (assistant) physicians, registered nurses, rural doctors and health workers], financial expenditures (total health expenditure), number of health institutions (hospitals, primary care institutions, professional public health institutions) and the prevalence of chronic diseases in middle-aged and elderly people in each province. Results There were significant differences in the prevalence of chronic diseases (χ2=57.900, P<0.001) and the number of chronic diseases (χ2=11.138, P=0.004) among the middle-aged and elderly people living in the eastern, central and western regions. Among the 14 types of chronic diseases, there were significant differences in the prevalence of chronic lung disease (χ2=30.906, P<0.001), liver disease (χ2=17.871, P<0.001), cerebrovascular disease (χ2=18.313, P<0.001), kidney disease (χ2=24.383, P<0.001), digestive system diseases (χ2=16.973, P<0.001), memory-related diseases (χ2=6.898, P=0.032) and asthma (χ2=22.055, P<0.001) in middle-aged and elderly people living in the eastern, central and western regions of China. The results of the multiple linear regression analysis showed that the overall prevalence of chronic diseases in middle-aged and elderly people was correlated with hospitals, primary care institutions, practicing (assistant) physicians, registered nurses, rural doctors and the equity of health financial expenditures in middle-aged and elderly people (P<0.05) . Conclusion There are regional differences in the prevalence of chronic diseases among the middle-aged and elderly populations in the eastern, central and western parts of China, and there are also certain differences in the investment in health care and the allocation of health care resources in different regions. Regional health management of major chronic diseases should be strengthened, the ability of disease prevention and health management in primary care should be improved, medical and health personnel should be strengthened, the regional health resources allocation balance should be improved, so as to shorten the regional differences in the prevalence of chronic diseases among middle-aged and elderly people in the eastern, central and western China.